A Didactic Strategy to Favor the Development of Oral Expression in Students at UEES and ECOTEC Universities - Ayala-Pazmino, Fabricio; Prieto-Lopez, Yeimer; Loor-Avila, Beatriz (Journal of language teaching and research, 2022)
The research attempts to solve some of the limitations students present in their oral expression in the university context, which causes scientific and academic production difficulties. An exhaustive bibliography related to the subject was consulted for its realization, and different instruments were applied. The use of theoretical methods and methodological background support the research. Furthermore, interviews and surveys were used to diagnose the current state of the development of oral expression in university students from UEES and ECOTEC. The results allowed the development of a set of activities to promote the development of the oral expression of these students. Additionally, based on the criteria offered by the discussion groups and experts, it was possible to verify the proposed strategies' effectiveness in educational practice. Oral communication appears as a necessary instrument for establishing relationships between man and the environment where he lives. Thus, it plays an essential role in forming and developing people's academic lives.